Treponema denticola: a pathogen in periodontal and pulp processes - Ramos Perfecto, Donald (2012)
The multifactorial etiology of periodontal disease and pulp processes, the bacterial factor has great relevance. In these processes is identified polymicrobial flora which highlights Treponema denticola, a spirochete with multiple virulence factors that make it a dangerous bacterium, being identified with a certain predominance in lesions as gingivitis necrotizing ulcer and acute apical abscesses. Its isolation culture is feasible by highly enriched media, although based procedures such as molecular biology PCR (polymerase chain reaction) can determine its presence and quantity. This review aims to tell us more about this pathogen.